2013
DOI: 10.3109/13561820.2013.829424
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education in a primary care teaching clinic: findings from a study involving pharmacy and medical students

Abstract: Interprofessional education (IPE) can be hindered by the lack of infrastructure required to support it. We developed a clinical IPE experience for medical and pharmacy students built upon an existing infrastructure. We created tools to orient students to IPE and had students participate in pharmacist-led and physician-led IPE clinics. Results from the surveys indicated that after participating in the IPE experience, there were no significant changes in attitudes toward interprofessional teamwork or attitudes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…Two of the three studies that reported no significant gains in teamwork included non-volunteer students, but in all three studies high baseline scores limited the potential for significant gains. Positive teamwork ratings measured in post-intervention only surveys were reported in several studies (Harris et al, 1998;O'Brien et al, 2013;Sicat et al, 2014). Florence et al (2007) reported significantly higher preparedness for interprofessional teamwork for those who had participated in interprofessional community placements compared to those who had not.…”
Section: Teamworkmentioning
confidence: 83%
See 2 more Smart Citations
“…Two of the three studies that reported no significant gains in teamwork included non-volunteer students, but in all three studies high baseline scores limited the potential for significant gains. Positive teamwork ratings measured in post-intervention only surveys were reported in several studies (Harris et al, 1998;O'Brien et al, 2013;Sicat et al, 2014). Florence et al (2007) reported significantly higher preparedness for interprofessional teamwork for those who had participated in interprofessional community placements compared to those who had not.…”
Section: Teamworkmentioning
confidence: 83%
“…Where pre-post-tests were available, significant gains in teamwork were reported in four studies (Florence et al, 2007;Leeper et al, 2001;McNair et al, 2005;Neill et al, 2007) and no significant change in three others (Dubouloz et al, 2010;Kuder et al, 2001;Sicat et al, 2014). In meta-analysis, the standardised mean difference (SMD) and 95% confidence interval (95% CI) were 0.62 (0.21, 1.04) in favour of post-test scores.…”
Section: Teamworkmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, interprofessional education (IPE), defined as a process where "two or more professions learn with, from and about each other in order to improve collaboration and the quality of care" (Barr, 2002., p6, footnote) is now part of the undergraduate curriculum for many different health care programmes (Art, De Roo, Willems, & De Maeseneer, 2008;Dando, d'Avray, Colman, Hoy, & Todd, 2012;Hamilton et al, 2008;Hylin, Nyholm, Mattiasson, & Ponzer, 2007;Jacobsen, Fink, Marcussen, Larsen, & Hansen, 2009;Moskowitz, Glasco, Johnson, & Wang, 2006;Reeves, Freeth, McCrorie, & Perry, 2002;Sicat, Huynh, Willett, Polich, & Mayer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Many types of IPE activities have been described, including meet-and-greet opportunities, didactic instruction, joint courses, case studies, web-based discussions, community service learning, clinical placements, studentled clinics, interaction with simulated or standardized patients, team-based case conferences, in-home medication reviews, and joint Objective Structured Clinical Examinations. [7][8][9][10][11][12][13][14][15][16][17][18] Olson and Bialorcerkowski's systematic review of various interprofessional activities suggested that the outcomes of these events may be dependent upon the context in which they are delivered. 19 Specifically, the evidence in this review supports that, in general, IPE events appear to be effective.…”
Section: Introductionmentioning
confidence: 99%